PESAN DAKWAH DALAM LIRIK LAGU RAMADAN KARYA MAHER ZAIN VERSI BAHASA INDONESIA ANALISIS WACANA KRITIS TEUN A. VAN DIJK - Safitri, Nurul; Pirol, Abdul; Sukirman, Sukirman (Fakultas Komunikasi dan Desain Program Studi Komunikasi dan Penyiaran Islam, 2025)
The main issue of this research is the da'wah messages contained in the lyrics of the Indonesian version of the song Ramadan by Maher Zain. This study aims to analyze the lyrics of Ramadan (Indonesian version) using Teun A. Van Dijk's discourse analysis model. This is a qualitative study employing the AWK model. Primary data were obtained from the song lyrics accessed through digital media, while secondary data were gathered from various references such as books, journals, theses, and relevant websites. Data collection techniques included analysis of text dimensions, social cognition, and social context according to Van Dijk’s model, as well as documentation in the form of video recordings and song texts. The findings reveal that at the macrostructure level, the song conveys da'wah messages such as the importance of fasting, the virtues of Ramadan, and calls for self-improvement. In terms of superstructure, the song is systematically composed with an inspiring introduction, content that touches on aspects of faith and social values, and a conclusion that invites spiritual reflection. At the microstructure level, the use of religious diction, repetitive language style, and metaphors enhances the da'wah messages and evokes spiritual emotions in the listeners. Additionally, the social context of the song is closely related to the global Muslim culture that celebrates Ramadan as a month of blessings and introspection.